Developmental changes in the perceived moral standing of robots - Reinecke, M (Elsevier, 2024)
Emerging evidence suggests that children may think of robots—and artificial intelligence, more generally—as having moral standing. In this paper, we trace the developmental trajectory of this belief. Over three developmental studies (combined N = 415) and one adult study (N = 156), we compared participants’ judgments (Experiments 1 - 3) and donation choices (Experiment 4) towards a human boy, a humanoid robot, and control targets. We observed that, on the whole, children endorsed robots as having moral standing and mental life. With age, however, they tended to deny experiential mental life to robots, which aligned with diminished ascription of moral standing. Older children’s judgments more closely mirrored those of adult participants, who overwhelmingly denied these attributes to robots. This sheds new light on children's moral cognitive development and their relationship to emerging technologies.